Recent Investigations on the Functionalizations of C(sp3)-H Bonds Adjacent to a Heteroatom - Cai, Xiao-Hua; Yang, Meng-Zhi; Xie, Bing (Letters in Organic Chemistry, 2019)
The selective functionalization of unactivated C(sp3)-H bonds has been regarded as an efficient and atom-economical approach for the formation of carbon-carbon or carbon-heteroatom bonds in modern organic synthesis. Especially, the oxidative activation of C(sp3)–H bonds adjacent to a heteroatom exhibits quite significant features in synthetic chemistry. For example, the direct functionalizations of amines, amides and ethers present important alternative tactics for the synthesis of various novel and useful molecules from simple starting materials. Many remarkable achievements in the area had continuously been made in the past decades. Here we reviewed recent investigations on the transformations of C(sp3)-H bond adjacent to a heteroatom.
Keywords: oxidative coupling